Lithium ion battery negative electrode with rapid lithium ion conducting material on surface and preparation method of lithium ion battery negative electrode

By preparing the lithium salt containing nitrate in the negative electrode material of the lithium-ion battery and converting it into lithium nitride during the charging and discharging process, a negative electrode electrode that quickly conducts lithium ion conduction is constructed, which solves the polarization and lithium dendrites of the lithium-ion battery during rapid charging, and improves the fast charging capability and cycle stability of the battery.

CN119852296APending Publication Date: 2025-04-18CHONGQING INNOVATION CENTER OF BEIJING INSTITUTE OF TECHNOLOGY +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411673743.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

Existing lithium-ion battery negative electrode materials are prone to polarization during fast charging, resulting in the actual capacity being lower than the theoretical value and easy to form lithium dendrites, increasing battery safety risks.

Method used

By preparing a lithium salt slurry containing nitrate and converting it into lithium nitride in situ during the first week of charging and discharging, a fast lithium ion conduction negative electrode at the interface of inorganic solid electrolytes is constructed.

Benefits of technology

This electrode structure can speed up the transmission speed of lithium ions, increase the desolvation speed, inhibit the formation of lithium dendrites, and improve the fast charging ability and cycle stability of the negative electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852296A_ABST
    Figure CN119852296A_ABST
Patent Text Reader

Abstract

The invention relates to the field of batteries, and discloses a lithium ion battery negative electrode with a rapid lithium ion conducting material on the surface and a preparation method thereof.The preparation method comprises the steps that slurry is prepared, the slurry comprises an adhesive, nitrate-containing lithium salt, a conductive agent, a negative electrode material and a solvent, a current collector is coated with the slurry and dried, and a prefabricated pole piece is obtained; the prefabricated pole piece, electrolyte and a counter electrode are assembled into a button cell, after first-cycle charging and discharging are carried out, nitrate-containing lithium salt in the prefabricated pole piece is converted into lithium nitride in situ, the lithium ion battery negative electrode is obtained, the window voltage of first-cycle charging and discharging is 0.01-1.5 V, the current density is 0.1 C (1C = 300mAh / g), and the temperature is 20-35 DEG C. According to the negative electrode prepared by the preparation method disclosed by the invention, at the temperature of 25 DEG C, the current density is 0.1 C (1C = 300mAh / g); and the specific capacity is not less than 250mAh / g after 200 cycles under the conditions that the window voltage is 0.01-1.5 V and the current density is 3C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of batteries, and in particular to a lithium ion battery negative electrode with a fast lithium ion conducting material on the surface and a preparation method thereof. Background Art

[0002] The development of electric vehicles plays a key role in building a sustainable green energy society as they help replace traditional fuel vehicles. The widespread use of electric vehicles is restricted by factors such as endurance issues and slow charging speeds, most of which are closely related to the performance of lithium-ion batteries. In lithium-ion batteries, graphite is one of the most commonly used negative electrode materials. Although its theoretical capacity is about 360mAh / g, polarization usually occurs during fast charging, resulting in an actual capacity lower than the theoretical value. In addition, lithium dendrites are easily formed on the graphite surface during fast charging, increasing battery safety risks such as fire or explosion.

[0003] The transport of lithium ions in graphite electrodes involves several key steps: 1) lithium ion transport in the electrolyte; 2) desolvation of lithium ions on the electrode surface; 3) lithium ion transport through the solid electrolyte interface membrane (SEI membrane); 4) lithium ion transport in the bulk phase of graphite. Among them, desolvation and lithium transport in SEI are considered to be rate-limiting steps. In order to solve the problems of severe graphite polarization, low capacity and lithium dendrites during fast charging, the academic community has conducted research from many aspects such as material structure, electrolyte design and surface engineering. The phosphorus coating layer constructed by the Sun team and the Ji team can be in situ transformed into a Li3P-based artificial SEI layer with excellent transport properties during the charge and discharge process, significantly improving the desolvation and diffusion rate of lithium ions and effectively inhibiting the formation of lithium dendrites. The preparation process of these improvement strategies is cumbersome and costly, and the development of simple and effective modification methods to promote lithium ion conduction still faces great challenges. Summary of the invention

[0004] The purpose of the present invention is to overcome the problems of low reversible specific capacity and poor cycle performance of existing negative electrode materials, and to provide a lithium ion battery negative electrode with a fast lithium ion conductive material on the surface and a preparation method thereof. The negative electrode has higher specific capacity and cycle stability than ordinary graphite negative electrodes under high current.

[0005] In order to achieve the above-mentioned object, the first aspect of the present invention provides a method for preparing a negative electrode of a lithium ion battery, wherein the preparation method comprises: preparing a slurry, wherein the slurry comprises a binder, a lithium salt containing nitrate, a conductive agent, a negative electrode material and a solvent, coating the slurry on a current collector and drying it to obtain a prefabricated electrode sheet, assembling the prefabricated electrode sheet with an electrolyte and a counter electrode into a button cell, and after the first cycle of charge and discharge, the lithium salt containing nitrate in the prefabricated electrode sheet is in situ converted into lithium nitride to obtain a negative electrode of a lithium ion battery;

[0006] The window voltage of the first cycle of charge and discharge is 0.01-1.5V, the current density is 0.1C (1C=300mAh / g), and the temperature is 20-35°C.

[0007] In the preparation method provided by the present invention, nitrate ions are converted into Li3N in situ during the lithiation process, and a negative electrode with a fast lithium ion conduction and a rich inorganic solid electrolyte interface is constructed. The electrode structure can accelerate the transmission speed of lithium ions, increase the desolvation speed, realize the rapid transmission of lithium ions at the interface, improve the fast charging capacity of the negative electrode, and reduce the risk of fast charging lithium precipitation. In addition, the electrode structure can also inhibit the formation of lithium dendrites under high current conditions.

[0008] A second aspect of the present invention provides a lithium ion battery negative electrode, which is prepared according to the preparation method described in the first aspect of the present invention.

[0009] Through the above technical scheme, the preparation method provided by the present invention, nitrate ions are converted into Li3N in situ during the lithiation process, and a negative electrode with fast lithium ion conduction and rich inorganic solid electrolyte interface is constructed. This electrode structure can accelerate the transmission speed of lithium ions, increase the desolvation speed, realize the rapid transmission of lithium ions at the interface, and improve the fast charging capability. In addition, this electrical structure can also inhibit the formation of lithium dendrites under high current conditions.

[0010] The negative electrode prepared by the present invention has a specific capacity of not less than 250 mAh / g, preferably not less than 300 mAh / g, and a cycle retention rate of not less than 80%, preferably not less than 90%, after 200 cycles at 25°C, a window voltage of 0.01-1.5V, and a current density of 3C. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 is a SEM image of the negative electrode prepared in Example 1;

[0012] Figure 2 is the EDS image of the negative electrode prepared in Example 1;

[0013] Figure 3 is the first week charge and discharge curve of the negative electrode prepared in Example 2;

[0014] Figure 4 dQ / dV curves of the negative electrode prepared in Example 3 and the negative electrode prepared in Comparative Example 1 in the first week;

[0015] Figure 5 It is a cycle performance diagram of the negative electrode prepared in Example 4 and the negative electrode prepared in Comparative Example 1. DETAILED DESCRIPTION

[0016] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0017] In addition, the term "and / or" in the specification and claims is used to describe the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.

[0018] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0019] The first aspect of the present invention provides a method for preparing a negative electrode of a lithium ion battery, wherein the preparation method comprises: preparing a slurry, wherein the slurry comprises a binder, a lithium salt containing nitrate, a conductive agent, a negative electrode material and a solvent, coating the slurry on a current collector and drying the slurry to obtain a prefabricated electrode sheet, assembling the prefabricated electrode sheet with an electrolyte and a counter electrode into a button cell, and after the first cycle of charge and discharge, the lithium salt containing nitrate in the prefabricated electrode sheet is in situ converted into lithium nitride to obtain a negative electrode of the lithium ion battery;

[0020] The window voltage of the first cycle of charge and discharge is 0.01-1.5V, the current density is 0.1C (1C=300mAh / g), and the temperature is 20-35°C.

[0021] The window voltage of the first week of charge and discharge is directly related to whether nitrate can be converted into lithium nitride in situ. The window voltage can be any value within the range of any two numbers among 0.01V, 0.05V, 0.1V, 0.2V, 0.3V, 0.5V, 0.7V, 1V, 1.3V, and 1.5V. If it is greater than 1.5V, nitrate cannot be converted into lithium nitride in situ.

[0022] The present invention has no special requirements for the type of adhesive, which can be a water-based adhesive or a solvent-based adhesive, and the corresponding solvent used can be water or an organic solvent. There are no special requirements for the types of electrolyte and counter electrode, as long as they can be assembled into button batteries according to conventional methods. For example, the electrolyte can be an ester-based electrolyte, and the specific solvent can be propylene carbonate, ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, etc.

[0023] The present invention has no special requirements for the drying method, for example, it can be vacuum dried at a temperature of 60-100° C. for 20-30 hours.

[0024] There is no special requirement for the type of conductive agent, such as acetylene black, 350G, carbon fiber, KS-6, SFG-6, graphene, etc.

[0025] When assembling into button cells, there are no special requirements for the counter electrodes, and any conventional counter electrodes can be used, such as lithium metal sheets, existing ternary material positive electrode sheets, lithium cobalt oxide positive electrode sheets, lithium manganese oxide positive electrode sheets, etc., which can all be purchased commercially.

[0026] In some embodiments, preferably, the mass ratio of the lithium salt containing nitrate to the adhesive is 0.05-0.5:1.

[0027] In some embodiments, preferably, the mass ratio of the lithium salt containing nitrate to the adhesive is 0.05-0.3:1.

[0028] The mass ratio of the lithium salt containing nitrate to the binder selected in the present invention can further improve the specific capacity and cycle stability of the negative electrode. The mass ratio of the lithium salt containing nitrate to the binder can be any value within the range of any two numbers of 0.05:1, 0.1:1, 0.2:1, 0.3:1, 0.4:1, and 0.5:1.

[0029] In some embodiments, preferably, the lithium salt containing nitrate includes lithium nitrate and / or lithium nitrite. The present invention selects nitrate as the anion of the lithium salt, which can be rapidly converted into lithium nitride in situ.

[0030] In some embodiments, preferably, the process of preparing the slurry comprises: dissolving the binder in the solvent, adding the lithium salt containing nitrate, and mixing to obtain a binder solution;

[0031] The binder solution, the conductive agent and the negative electrode material are uniformly stirred to obtain the slurry.

[0032] By first mixing the adhesive and nitrate to obtain an adhesive solution, and then mixing the solution with a conductive agent and a negative electrode material, the adhesive and the lithium salt containing nitrate can be mixed more evenly, and the lithium nitride in the negative electrode can be further distributed more evenly, thereby further improving the electrochemical performance of the negative electrode. The present invention has no special requirements for the amount of solvent used, as long as the adhesive and the lithium salt containing nitrate can be dissolved, such as after the adhesive and the lithium salt containing nitrate are mixed, the total mass of the solvent, the adhesive and the lithium salt containing nitrate is fixed to 15-20 times the mass of the adhesive by adding a solvent. The present invention has no special requirements for the mixing method, as long as the materials can be mixed evenly, such as stirring and mixing, the stirring speed can be 500-1000rpm, and the time can be 20-30h.

[0033] In some embodiments, preferably, based on the total amount of the adhesive solution, the mass fraction of the adhesive is 1-10wt%. The amount of adhesive used affects the firmness of the adhesive bond with other materials, affects the distribution uniformity of the material, and the mass fraction of the adhesive can be any value within the range of any two of 1wt%, 2wt%, 3wt%, 5wt%, 7wt%, 8wt%, 9wt%, and 10wt%.

[0034] In some embodiments, preferably, the adhesive includes polyacrylic acid and / or sodium carboxymethyl cellulose, and the solvent is water.

[0035] In some embodiments, preferably, the weight average molecular weight of the polyacrylic acid is 200,000-800,000; the weight average molecular weight of the sodium carboxymethyl cellulose is 50,000-200,000.

[0036] In some embodiments, preferably, the coating thickness of the slurry is 30-60 microns.

[0037] In some embodiments, preferably, the current collector is selected from any one of copper foil, aluminum foil, nickel foil, copper mesh, aluminum mesh and nickel mesh.

[0038] In some embodiments, preferably, based on the total amount of the slurry, the amount of the negative electrode material is 70-90wt%, the amount of the binder is 10-20wt%, and the amount of the conductive agent is 5-10wt%. Based on the total amount of the slurry, the amount of the negative electrode material can be any value within the range of 70wt%, 75wt%, 80wt%, 85wt%, and 90wt%; the amount of the binder can be any value within the range of 10wt%, 12wt%, 15wt%, 18wt%, and 20wt%; the amount of the conductive agent can be any value within the range of 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, and 10wt%.

[0039] In some embodiments, preferably, the negative electrode material is selected from any one of a graphite negative electrode material, a silicon negative electrode material or a metal oxide negative electrode material.

[0040] The present invention has no particular restriction on the type of graphite negative electrode material, and any existing graphite negative electrode can be used, such as natural graphite, artificial graphite, or modified graphite with a coating layer; similarly, there is no particular restriction on silicon negative electrode materials and metal oxide negative electrode materials, and any existing silicon negative electrode materials and metal oxide negative electrode materials can be used, wherein the silicon negative electrode material can be nano-silicon, micron silicon, and silicon oxide, and the metal oxide negative electrode material can be iron oxide, nickel oxide, etc.

[0041] A second aspect of the present invention provides a lithium ion battery negative electrode, which is prepared according to the preparation method described in the first aspect of the present invention.

[0042] In some embodiments, preferably, the negative electrode of the lithium ion battery has a specific capacity of not less than 300 mAh / g after 200 cycles at a window voltage of 0.01-1.5 V and a current density of 3C.

[0043] The negative electrode structure with nitrate ions prepared by the method provided by the present invention is that the nitrate ions are converted into Li3N in situ during the lithiation process, and a negative electrode with fast lithium ion conduction and rich inorganic solid electrolyte interface is constructed. The electrode structure accelerates the transmission speed of lithium ions, increases the desolvation speed, realizes the rapid transmission of lithium ions at the interface, and improves the fast charging capability. In addition, the electrode structure can inhibit the formation of lithium dendrites under high current conditions.

[0044] The method provided by the invention is simple and easy to operate, has low cost, and the prepared negative electrode has good electrochemical performance.

[0045] According to a particularly preferred embodiment of the present invention, the preparation method comprises: preparing a slurry, wherein the slurry comprises a binder, a lithium salt containing nitrate, a conductive agent, a negative electrode material and a solvent, coating the slurry on a current collector and drying the slurry to obtain a prefabricated electrode sheet, assembling the prefabricated electrode sheet with an electrolyte and a counter electrode into a button cell, and after the first week of charge and discharge, the lithium salt containing nitrate in the prefabricated electrode sheet is in-situ converted into lithium nitride to obtain a negative electrode of a lithium ion battery;

[0046] The window voltage of the first cycle of charge and discharge is 0.01-1.5V, the current density is 0.1C (1C=300mAh / g), the temperature is 25°C, the mass ratio of the lithium salt containing nitrate to the adhesive is 0.1-0.3:1, and the mass fraction of the adhesive is 1-5wt% based on the total amount of the adhesive solution.

[0047] The present invention will be described in detail below by way of examples. In the following examples and comparative examples, unless otherwise specified, the reagents or instruments used without indicating the manufacturer are conventional products that can be purchased commercially. If no specific conditions are indicated in the examples, the conventional conditions or the conditions recommended by the manufacturer are followed.

[0048] The conductive agent is acetylene black;

[0049] Ester-based electrolyte: 1M LiPF6 in ethylene carbonate, wherein the solvent is ethylene carbonate and the solute is LiPF6;

[0050] The weight average molecular weight of polyacrylic acid is 450,000;

[0051] The weight average molecular weight of sodium carboxymethyl cellulose is 120,000.

[0052] The constant current charge and discharge test of the battery was carried out using Land CT2001A produced by Wuhan Landian Electronics Co., Ltd.

[0053] Example 1

[0054] (1) Weigh 0.5 g of polyacrylic acid (adhesive) and dissolve it in an aqueous solution, weigh 0.05 g of lithium nitrate and add it, then continue to add water to make the total volume 10 g, and stir magnetically at 800 rpm for 24 hours to mix well, to obtain an adhesive solution.

[0055] (2) Weigh the adhesive solution, conductive agent and graphite prepared in step (1) as required, so that the mass ratio of the adhesive to the conductive agent and graphite in the adhesive solution is 1:1:8, stir at 800 rpm for 2 h to prepare a slurry, apply the slurry on a copper foil with a coating thickness of 40 μm, and vacuum dry the coated copper foil in an oven at 80° C. for 24 h to obtain a prefabricated electrode.

[0056] (3) The prefabricated electrode sheet is combined with an ester-based electrolyte and lithium metal to form a 2032 button cell, and the first week of charge and discharge is carried out at 25° C., 0.1C (1C=300mAh / g) current density, and a window voltage of 0.01-1.5V. The lithium nitrate in the prefabricated electrode sheet is converted into lithium nitride in situ to obtain a lithium ion battery negative electrode with a fast lithium ion conductive material.

[0057] Figure 1 This is a SEM image of the natural negative electrode after the first week of charge and discharge of the negative electrode prepared in this example. It can be seen that there is no obvious particle aggregation on the graphite surface, indicating that a uniform SEI layer has been formed on the graphite surface. Figure 2This is the EDS spectrum of the negative electrode after the first cycle. It can be seen that the F, N, C, and O elements are evenly distributed on the graphite surface, indicating that a uniform solid electrolyte interface containing lithium nitride is formed on the graphite surface. In addition, the presence of lithium nitride is also verified by performing XPS scanning on the negative electrode prepared in this embodiment.

[0058] Example 2

[0059] (1) Weigh 0.5 g of polyacrylic acid and dissolve it in an aqueous solution, weigh 0.15 g of lithium nitrate and add it, then continue to add water to make the total volume 10 g, and stir magnetically at 1000 rpm for 20 h to mix evenly, to obtain an adhesive solution.

[0060] (2) Weigh the adhesive solution, conductive agent and graphite prepared in step (1) as required, so that the mass ratio of the adhesive to the conductive agent and graphite in the adhesive solution is 1:1:8. After sampling, stir at 1000 rpm for 2 h to prepare a slurry. Apply the slurry on a copper foil with a coating thickness of 60 μm. Vacuum dry the coated electrode in an oven at 80° C. for 24 h to obtain a prefabricated electrode.

[0061] (3) The prefabricated electrode is combined with an ester-based electrolyte and lithium metal to form a 2032-type button battery, and the first week of charge and discharge is carried out at 25° C., 0.1C (1C=300mAh / g) current density, and a window voltage of 0.01-1.5V. The lithium nitrate in the prefabricated electrode is converted into lithium nitride in situ to obtain a lithium ion negative electrode with a fast ion conductive network.

[0062] Figure 3 The first cycle charge and discharge curves of the negative electrode (red curve) prepared in this embodiment and the negative electrode (black curve) prepared in comparative example 1 are shown. It can be seen that the first cycle coulomb efficiency of the negative electrode prepared in this embodiment is improved, which may be because the method provided by the present invention inhibits the decomposition of the electrolyte.

[0063] Example 3

[0064] (1) Weigh 0.5 g of polyacrylic acid and dissolve it in an aqueous solution, weigh 0.25 g of lithium nitrate and add it, then continue to add water to make the total volume 10 g; stir magnetically at 800 rpm for 24 hours to mix evenly, and obtain an adhesive solution.

[0065] (2) Weigh the adhesive solution, conductive agent and graphite prepared in step (1) as required, so that the mass ratio of the adhesive to the conductive agent and graphite in the adhesive solution is 1:1:8, stir at 800 rpm for 2 h to prepare a slurry, apply the slurry on a copper foil with a coating thickness of 30 μm, and vacuum dry the coated electrode in an oven at 80° C. for 24 h to obtain a prefabricated electrode.

[0066] (3) The prefabricated electrode is combined with an ester-based electrolyte and lithium metal to form a 2032-type button battery, and the first week of charge and discharge is carried out at 25° C., 0.1C (1C=300mAh / g) current density, and a window voltage of 0.01-1.5V. The lithium nitrate in the prefabricated electrode is converted into lithium nitride in situ to obtain a lithium ion negative electrode with a fast ion conductive network.

[0067] Figure 4 The first-cycle dQ / dV curves of the graphite negative electrode (black curve) prepared in Comparative Example 1 and the negative electrode (red curve) prepared in this embodiment are shown in Figure 1. It can be seen that the oxidation potential of the negative electrode prepared in the present invention is relatively lower, indicating that the negative electrode prepared in this embodiment has weaker polarization, which is conducive to the performance of rate performance.

[0068] Example 4

[0069] (1) Weigh 0.5 g of polyacrylic acid and dissolve it in an aqueous solution, weigh 0.35 g of lithium nitrate and add it, then continue to add water to make the total volume 10 g, and stir magnetically at 800 rpm for 24 hours to mix evenly, to obtain an adhesive solution.

[0070] (2) Weigh the adhesive solution, conductive agent and graphite prepared in step (1) as required, so that the mass ratio of the adhesive to the conductive agent and graphite in the adhesive solution is 1:1:8, stir at 800 rpm for 2 h to prepare a slurry, apply the slurry on a copper foil with a coating thickness of 40 μm, and dry the coated electrode in a vacuum oven at 80° C. for 24 h.

[0071] (3) The prefabricated electrode is combined with an ester-based electrolyte and lithium metal to form a 2032-type button battery, and the first week of charge and discharge is carried out at 25° C., 0.1C (1C=300mAh / g) current density, and a window voltage of 0.01-1.5V. The lithium nitrate in the prefabricated electrode is converted into lithium nitride in situ to obtain a lithium ion negative electrode with a fast ion conductive network.

[0072] Figure 5 The graphs are the cycle diagrams of the graphite negative electrode (black curve) prepared in comparative example 1 and the negative electrode (red curve) prepared in this embodiment for charge and discharge tests at 25°C, 3C current density, and a window voltage of 0.01-1.5V. It can be seen that after 200 cycles, the negative electrode prepared in this embodiment can still maintain a high specific capacity of more than 300mAh / g at 3C, while the graphite in comparative example 1 can only exert a specific capacity of about 200mAh / g.

[0073] Example 5

[0074] The process was carried out in the same manner as in Example 1, except that the amount of polyacrylic acid was 1 g, and 0.05 g of lithium nitrate was replaced by 0.05 g of lithium nitrite.

[0075] Example 6

[0076] The method of Example 1 is followed, except that the mass ratio of the adhesive to the conductive agent and graphite is 1:0.5:8.5.

[0077] Example 7

[0078] The method of Example 1 is followed, except that the mass ratio of the adhesive to the conductive agent and graphite is 2:1:7.

[0079] Comparative Example 1

[0080] The process is carried out in the same manner as in Example 1, except that lithium nitrate is not added in step (1), thereby obtaining a graphite negative electrode.

[0081] Comparative Example 2

[0082] The method of Example 1 is followed, except that the window voltage of the first cycle of charge and discharge is 0.5-2.5V.

[0083] The button cells assembled from the above Examples 1-7 and Comparative Examples 1 and 2 were activated for 3 cycles at 25°C, a window voltage of 0.01-1.5V, and 0.1C, and then charge and discharge tests were performed at a current density of 3C (1C = 300mAh / g) and a window voltage of 0.01-1.5V. The electrochemical properties after 200 cycles are shown in Table 1.

[0084] Table 1 Electrochemical performance test results

[0085]

[0086]

[0087] It can be seen from the results of Table 1 that, using Examples 1-4 of the present invention, the mass ratio of nitrate ions compared to graphite materials gradually increases, and compared to Comparative Example 1, the appropriate ratio of nitrate ions is conducive to forming a fast lithium ion network, improving rate performance and capacity retention. Excessive nitrate ion ratio is not conducive to improving rate performance and capacity retention. Examples 5-7 change the ratio of binder, and the appropriate ratio of binder promotes the uniform distribution of the lithium nitride fast ion conduction network, thereby affecting the rate performance.

[0088] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a negative electrode of a lithium ion battery, characterized in that: The preparation method comprises: preparing a slurry, wherein the slurry comprises a binder, a lithium salt containing nitrate, a conductive agent, a negative electrode material and a solvent; coating the slurry on a current collector and drying the slurry to obtain a prefabricated electrode sheet; assembling the prefabricated electrode sheet with an electrolyte and a counter electrode into a button battery; and after the first cycle of charge and discharge, converting the lithium salt containing nitrate in the prefabricated electrode sheet into lithium nitride in situ to obtain a negative electrode of a lithium ion battery; The window voltage of the first cycle of charge and discharge is 0.01-1.5V, the current density is 0.1C (1C=300mAh / g), and the temperature is 20-35°C.

2. The preparation method according to claim 1, wherein The mass ratio of the lithium salt containing nitrate to the adhesive is 0.05-0.5:1, preferably 0.05-0.3:

1.

3. The preparation method according to claim 1 or 2, wherein The lithium salt containing nitrate includes lithium nitrate and / or lithium nitrite.

4. The preparation method according to any one of claims 1 to 3, wherein The process of preparing the slurry comprises: dissolving the adhesive in the solvent, adding the lithium salt containing nitrate, mixing, and obtaining an adhesive solution; The binder solution is stirred evenly with the conductive agent and the negative electrode material to obtain the slurry; Preferably, based on the total amount of the adhesive solution, the mass fraction of the adhesive is 1-10 wt %.

5. The preparation method according to any one of claims 1 to 4, wherein: The adhesive includes polyacrylic acid and / or sodium carboxymethyl cellulose, and the solvent is water; Preferably, the weight average molecular weight of the polyacrylic acid is 200,000-800,000; the weight average molecular weight of the sodium carboxymethyl cellulose is 50,000-200,000.

6. The preparation method according to any one of claims 1 to 5, wherein: The coating thickness of the slurry is 30-60 microns; And / or, the current collector is selected from any one of copper foil, aluminum foil, nickel foil, copper mesh, aluminum mesh and nickel mesh.

7. The preparation method according to any one of claims 1 to 5, wherein: Based on the total amount of the slurry, the amount of the negative electrode material is 70-90wt%, the amount of the binder is 10-20wt%, and the amount of the conductive agent is 5-10wt%.

8. The preparation method according to any one of claims 1 to 7, wherein: The negative electrode material is selected from any one of graphite negative electrode material, silicon negative electrode material or metal oxide negative electrode material.

9. A negative electrode for a lithium ion battery, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 8.

10. The lithium ion battery negative electrode according to claim 9, wherein: The negative electrode of the lithium ion battery has a specific capacity of not less than 300 mAh / g after 200 cycles at a window voltage of 0.01-1.5 V and a current density of 3C.

Citation Information

Patent Citations

  • Negative electrode for improving rate capability of lithium ion energy storage device and application of negative electrode

    CN110838575A

  • Sodium nitrate-containing sodium ion battery negative pole piece as well as preparation method and application thereof

    CN115548263A

  • Electrolyte with low interface impedance and preparation method of lithium ion battery

    CN116505089A

  • Graphite negative electrode material, fast-charging graphite negative electrode material, composite electrode, preparation method of composite electrode, lithium ion battery and electric equipment

    CN118198338A

  • Water-based positive pole piece composition containing water-soluble lithium-containing compound, and secondary battery

    WO2023245484A1